Stapled Hemorrhoidectomy: A Safe Procedure for Third and Fourth Grade Hemorrhoids - Muhammad Tahir Ali, Munawer Latif Memon, Farrukh Sami, Muhammad Hanif Memon, Muhammad Tariq Khan, Javaid Sajjad Hashmi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the safety outcome of staple hemorrhoidectomy in grade III and IV hemorrhoids. Study Design: Descriptive study Place and Duration of Study: Department of Surgery, Shahida Islam Medical Complex, Lodhran from 1st July 2020 to 30th June 2021. Methodology: Seventy patients were selected who were suffering from third or fourth grade hemorrhoids. The age of the patients was between 21-56 years with both gender been presented. Longos method was opted with spinal analgesic been delivered in lithotomy positioning. The complete surgical protocol was maintained with preoperative antibiotic deliverance. The procedure took 30-50 minutes. Patient was then kept in recovery room for three hours post operation and all postoperative antibiotics were timely administered. Results: Mean age of study participants was 41.2±3.2. Men appeared to be higher in number as compared to women. Grade III patients were more in number as compared to grade IV. Most common complication which was observed in present study is postoperative pain. Majority of the patients (70%) showed no associated complications. Conclusion: Staple hemorrhidectomy is appeared to be a safe and reliable surgical procedure for the treatment of grade III and grade IV hemorrhoids. Keywords: Hemorrhoids, Surgical procedure, Stenosis, Efficacy, Conventional